Syntheses and antitumor targeting G1 phase of the cell cycle of benzoyldihydroisoquinolines and related 1-substituted isoquinolines - Bermejo, Almudena (2002)
A series of 1-substituted 3,4-dihydroisoquinolines were synthesized and tested in vitro against the leukemia L 1210 cell line to evaluate their ability to perturb the cell cycle by arresting cells in the G1 phase. 1-Benzoylimines, 1-phenylimines, and 1-alkylimines were synthesized. The most powerful cytotoxic derivatives, 1-benzoyl-3,4-dihydroisoquinolines (1-26), were obtained from amides I via 1-benzyl-3,4-dihydroisoquinoline in good yield by a direct selective oxidation of the benzylic carbon of the corresponding imines through 10% Pd/C in acetonitrile. SAR studies let us to identify the essential structural features for cytotoxic activity. The most bioactive compounds (with IC50 < 5μM) were BzDHIQ (13, 22, 21, 8, 9, 11, 1, 20, 6, and 19), and they are characterized by the following: (i) An α-ketoimine moiety is necessary for potent antiproliferative activity (1-phenyl- and 1-alkyl-3,4-dihydroisoquinoline derivatives, 34-40, are less active). (ii) An hydrophobic, benzyloxy, alkyloxy, or allyloxy group at the C-6 position seems to be relevant for cytotoxicity. (iii) Regarding the influence of the benzoylic moiety, both the unsubstituted (13, 8, 9, 11, 1, and 6) and the 3′-monosubstituted (22, 21, 20, and 19) compounds were more potent than compounds with other substitutions.